Cardiovascular risk factors awareness and prevalence among primary care physicians: an insight from the West region Awareness Initiative Survey to fight cardiovascular disease (WAIT-CVD) in Cameroon. (December 2015) - Jingi, Ahmadou; Noubiap, Jean
Abstract Background Data on the frequency and awareness of cardiovascular risk factors in practicing doctors are lacking in Cameroon. This study reports on the prevalence of cardiovascular risk factors in primary care physicians (PCPs) at the forefront for the fight against chronic diseases, and the implications for cardiovascular disease prevention and management. Methods We carried out a cross-sectional study in the west region of Cameroon. Participants were recruited from 111 PCPs who lived and worked in the region at the time of the study. Data were collected on designed questionnaires adapted from the WHO STEPS approach in two steps, and a nurse-led examination was performed. Results Sixty five (65) consenting doctors, aged 39.1 (SD 8.9) years, with 45 (69.2 %) males, were included. Self-reported hypertension rate was 4.6 % (n = 3). The frequency of pre-hypertension was 21.5 % (n = 14) and of hypertension was 26.2 % (n = 17). Self-reported diabetes rate was 3.1 % (n = 2). The frequency of overweight was 46.2 % (n = 30), and obesity was 23.1 % (n = 15). Eight (12.3 %) participants were smokers, 25 (38.5 %) had excessive alcohol consumption (more than two drinks per day for men and one drink per day for women) and 54 (83.1 %) practiced physical exercise, although below the recommendations. Positive family history any CVD was reported in 52.4 % (39.4–65.1). Up to 35.4 % (23.9–48.2) have never done their lipid profile test. There was no difference in cardiovascular risk factors between males and females, except for systolic blood pressure (p  < 0.001) and diastolic blood pressure (p  = 0.002) that were higher in males. No significant difference was noted in the other risk profiles and the rate of awareness between sexes. Conclusion There are high prevalence of cardiovascular risk factors with low awareness among PCPs in the West region of Cameroon. This is alarming as doctors at the fore front for the fight against cardiovascular diseases are not aware of their own risk profile. There is need for more awareness programs targeting doctors so as to prevent a sick population with sick doctors.